Factors Affecting Internet Banking on Customer Satisfaction: A Case Study Based on a Commercial Bank, Sri Lanka - Dankumbura, S. H.; Gunasekera, A. L. (Department of Finance Faculty of Commerce and Management Studies University of Kelaniya, 2020)
Introduction - Internet banking is a major role in banking industry and the regulatory body. The purpose of this study is to determine the factors affecting internet banking on customer satisfaction by considering customer awareness, security and privacy, and service quality. Design/Methodology/Approach - A survey was conducted for data collection through a pre-tested questionnaire distributed a one of Commercial Bank, Head office branch, Sri Lanka. The study follows the Simple random sampling method to collect data, the researcher has distributed 300 questionnaires and 284 responses have been received. Descriptive Statistics, Cronbach's alpha, Test of homogeneity of variance and Multiple Regression were used for data analysis and SPSS has been used as statistical software to analyse the survey data. Findings – According to the research findings majority of internet banking users belongs to the age group of 18-25 years. And also findings revealed that, customer awareness, security and privacy, and service quality affect internet banking customer satisfaction positively and significantly. Conclusion - The study fulfils the existing research gap in the area of service quality and other factors which are affecting to the internet banking. This research can help internet banking providers to know internet banking users’ opinion and also find the solutions through customers’ perspective. These findings will help for future studies relating to internet banking and customer satisfaction.
Keywords: Internet Banking, Customer Satisfaction, Customer Awareness, Security and Privacy, Service Quality